Новые род и вид яйцееда (Hymenoptera, Scelionidae) с юга УССР - Кононова, С.В. (Вестник зоологии, 1982)
A description of Latonius gen. nov. and Latonius planus sp. A number of characters, such as general body shape. antennal structure, position of the oculi show similarity of the new genus ot Aradoplagus; smaller body size, number of antennal segments,wing venationand pubescencemake it similarto Telenomus,leg structure- to Protelenomus. Type m a t e r i a l is deposited in the collection of the Institute of Zoology, Ukrainian S. S. R. Academy of Sciences.